1991
DOI: 10.2169/internalmedicine1962.30.21
|View full text |Cite
|
Sign up to set email alerts
|

A study of the clinical significance of lipoprotein (a) in nephrotic syndrome.

Abstract: Lipoprotein (Lp)(a) concentrations were measured in eight patients with nephrotic syndrome in the age range of 8 to 69 yrs. Mean(± SE) levels of serum Lp(a) were elevated in the nephrotic patients compared to controls (76.5 ± 19.7 vs 18.6 ± 0.9 mg/dl, p <0.001). After treatment with prednisolone, Lp(a) concentrations were decreased from 85.2 ±21.6 to 42.2 ± 14.0 mg/dl. During the treatment, serum total cholesterol showed a negative correlation with serumalbuminconcentration. However, no correlation wasnoted be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Elevations in Lp(a) serum levels have been documented in adults with proteinuria (24)(25)(26), adults with end-stage renal failure treated by hemodialysis (27), renal allograft recipients (28), and children (33) and adults (34) with diabetes mellitus. In addition, alcohol intake (35) and possibly treatment with corticosteroids (25) may have an effect on serum Lp(a) levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevations in Lp(a) serum levels have been documented in adults with proteinuria (24)(25)(26), adults with end-stage renal failure treated by hemodialysis (27), renal allograft recipients (28), and children (33) and adults (34) with diabetes mellitus. In addition, alcohol intake (35) and possibly treatment with corticosteroids (25) may have an effect on serum Lp(a) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Lp(a) can be detected in umbilical cord blood and serum of newborns (20)(21)(22), and a gradual rise in serum levels has been observed between the ages of 2 and 13 y (23). Previous studies in adults reported increased Lp(a) levels in patients with proteinChronic renal disease is often accompanied by severe dyslipi- (24)(25)(26) and in patients treated with hemdialysis (27) and demia, a known risk factor for cardiovascular disease. In adults, renal transplantation (28).…”
Section: ~H~ Distribution Of Lp(a) Levels In Normal Subjects Wasmentioning
confidence: 99%
“…Among the environmental factors that certainly play a role in determining plasma concentrations, renal diseases are one of the best documented. Lp(a) levels have been reported to be elevated in kidney hemodialysis patients [23][24][25][26][27][28][29][30][31][32], where they appear to be an independent risk factor for cardiovascular disease [33], in untreated patients with end-stage renal failure [34][35][36][37][38][39], and in pro teinuric syndromes [40][41][42][43][44][45]. Renal transplantation in endstage renal disease partially corrects the abnormality [25,46], A correlation of Lp(a) levels with the degree of protein uria has indeed been suspected, with the hypothesis that the decrease in scrum albumin leads to an increased hepat ic Lp(a) synthesis [43], Omega-3 fatty acids (co-3 FA) have recently been pro posed as a useful adjunct therapy in patients with renal disease [47] where they may correct some of the lipid abnormalities (notably the hypertriglyceridemia [48]) and favorably alter renal vasodilatory reserve [49], We have recently reported that a 6-week course of dietary supple mentation with co-3 FA reduces proteinuria in patients with membranous glomerulonephritis and focal glomeru lar sclerosis [50].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that Lp(a) levels are significantly elevated in patients with nephrotic syndrome [8][9][10][11][12][13][14][15][16][17][18]. However, it was never systematically investigated whether and how the apo(a) kringle-IV repeat polymorphism contributes to this increase.…”
mentioning
confidence: 99%